Implementation of Religious Moderation of KPM IAIN Students Parepare, Batulappa Sub-District, Holds A Praise Safari - Satar, Muhammad; Pangestu, Dian Resky; Tenriyati, Tenriyati; Asrida (Makkareso: Riset Pengabdian Masyarakat, 2023)
This research focuses on the implementation of religious moderation through the KPM IAIN Parepare Student Da'wah Safari activities in the Batulappa District. The study aims to understand and promote religious teachings that are fair, balanced, and correctly aligned with the nature of human beings, characterized by monotheism and faith in their spirits. The research methodology involved in-depth observations and analysis conducted by KPM students, who adjusted their work programs based on the observed needs and capacities of the community. The findings reveal that religious moderation encompasses harmonious relationships between humans and their Lord, fostering a close connection to God through activities such as congregational prayers and the Talim Council. Additionally, religious moderation emphasizes the importance of human relations (hablumminannas), leading to a harmonious society where community bonds are strengthened through social assistance and collaborative efforts. Furthermore, the study highlights the significance of integrating religious moderation with nature, including responsible waste management and reforestation activities. The concept of religious moderation does not endorse hostility or hatred but emphasizes collaboration as a means to eliminate evil and promote a better society.